2022
DOI: 10.1186/s12905-022-01796-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations between depressive symptoms, socio-economic factors, traumatic exposure and recent intimate partner violence experiences among women in Zimbabwe: a cross-sectional study

Abstract: Background Population-based research on the cumulative effects of socio-economic conditions and trauma exposures, particularly women’s experiences of intimate partner violence (IPV) on their mental health in Zimbabwe, has been limited. Aim Our study aimed to determine the associations between depressive symptoms and socio-economic factors, IPV, and traumatic exposures among a nationally representative sample of women from Zimbabwe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Women were also primarily responsible for purchasing, cooking, and serving food to their families while eating last, and the inability to fulfill these tasks increased the risk of intimate partner violence [56,74,75]. This, in turn, could further impact their mental health [76][77][78]. The association between food insecurity and mental health can be more pronounced for men due to the role of men in some patriarchal societies.…”
Section: Gendermentioning
confidence: 99%
“…Women were also primarily responsible for purchasing, cooking, and serving food to their families while eating last, and the inability to fulfill these tasks increased the risk of intimate partner violence [56,74,75]. This, in turn, could further impact their mental health [76][77][78]. The association between food insecurity and mental health can be more pronounced for men due to the role of men in some patriarchal societies.…”
Section: Gendermentioning
confidence: 99%
“…Subsequent studies have also found that women with experiences of IPV and poorer health outcomes are also more likely to be living on low incomes or lower incomes than prior to IPV ( Loxton et al, 2017 ; Wathen et al, 2018 ). Studies of accessing help also revealed women on low incomes were overrepresented among survivors and how this influences what services they can even access in some countries, for example, in the United States where mental health services may only be available to those who can afford to pay ( Machisa & Shamu, 2022 ; Wadsworth et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, a recent population survey was conducted with 2905 women aged 18+ to investigate the associations between depressive symptoms and socioeconomic factors, IPV and other variables [27]. They found 15% of the women self-reported depressive symptoms, and higher rates of depressive symptoms were linked with experiences of intimate partner violence (IPV) and lower socio-economic status, amongst other things.…”
Section: Introductionmentioning
confidence: 99%